PTH-114 Infection in Severe Alcoholic Hepatitis: Results from The Stopah Trial. (17th August 2016) - Atkinson, S; Vergis, N; Thursz, M; ,
Abstract : Introduction: Severe alcoholic hepatitis (SAH; mDF ≥ 32) is often complicated by infection. In the recent trial STOPAH, prednisolone was associated with a doubling of the numbers of infections classified as serious adverse events (SAEs). We sought to identify the determinants of infection and the impact of infection on mortality. Methods: Data regarding infection were collected weekly during admission and at all trial visits; SAE reports were included. Incident infection was defined as new infection occurring after treatment start. The follow-up period considered was 120 days. Results: Data from 1093 cases were available. 127 patients were infected at baseline; this was not associated incident infection (p = 0.51) or 90 day mortality (p = 0.19). 308 patients developed an incident infection; 100 were reported as SAEs. As in other studies in SAH median time to infection was 13 days. Age (p = 0.015), WHO performance status (PS; p = 0.007), WBC (p = 0.002), INR (p = 0.023) and creatinine (p = 0.02) at baseline were associated with incident infection. On multivariate analysis PS (p = 0.02) and WBC (p = 0.00016) remained associated. DF (p = 0.011) and GAHS (p = 0.003) but not MELD (p = 0.41) associated with incident infection. Lille score was associated with incident infection after day 7 (p = 0.013). However, infection within 7 days was itself associated with Lille non-response (p = 0.008, OR 1.78 [95%CI 1.32–2.40]), independent of prednisolone treatment. Although infections classified as SAEs were more common in the prednisolone treated group (p = 0.001, OR 2.51 (95%CI 1.46–4.30). There was no association between prednisolone and all incident infections occurring during treatment (p = 0.88), but prednisolone was associated with infection in the post-treatment period (p = 0.023, OR 1.92 [95% CI, 1.10–3.35]). Incident infection was associated with 28 (p < 0.001) and 120 day mortality (p = 0.001). This was independent of prednisolone therapy and Lille response. Prednisolone-treated Lille non-responders had a higher rate of incident infection at day 120 (49% vs 27%; p < 0.0001). Conclusion: In SAH incident infection is associated with mortality independently of early improvement in liver function measured by Lille. Very early onset of infection is associated with classification as a Lille non-responder. Thus in some instances Lille non-response may represent untreated infection not steroid treatment-failure. An association between prednisolone and post-treatment infection may explain the catch-up mortality after 28 days and fleeting benefit of prednisolone seen in STOPAH. Disclosure of Interest: None Declared